2014
DOI: 10.4103/0253-7613.135951
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein offers cardioprotection in rats with simultaneous type 2 diabetes and renal hypertension

Abstract: Objectives:The study aimed at examining the role of oxidative stress in cadioprotective effects of oleuropein in a rat model of simultaneous type 2 diabetes and renal hypertension.Materials and Methods:Five groups of male Sprague-Dawley rats including a control group, a diabetic-hypertensive group receiving vehicle, and three diabetic-hypertensive groups receiving oleuropein at 20, 40, or 60 mg/kg/day were used. Blood pressure and glucose, serum malondialdehyde, and erythrocyte superoxide dismutase were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
(30 reference statements)
0
34
0
Order By: Relevance
“…Angiotensin 2 is a known vasoconstrictor, and it also protected rat hearts from reperfusion injury, which is usually associated with oxidative stress (Bali et al, ; M. Esmailidehaj et al, ; M. Esmailidehaj et al, ; Manna et al, ). In rats with simultaneous hypertension and diabetes, left ventricular developed pressure and rate of rise and rate of decrease of ventricular pressure was also found to be lower with oleuropein treatment than with the control in one study (A.A. Nekooeian, Khalili, Khosravi, ). A daily supplementation of ~30 mg was also found to reduce both systolic and diastolic blood pressure in women (Moreno‐Luna et al, ).…”
Section: Role Of Oleuropein In Treatment Of Metabolic Syndromementioning
confidence: 91%
See 2 more Smart Citations
“…Angiotensin 2 is a known vasoconstrictor, and it also protected rat hearts from reperfusion injury, which is usually associated with oxidative stress (Bali et al, ; M. Esmailidehaj et al, ; M. Esmailidehaj et al, ; Manna et al, ). In rats with simultaneous hypertension and diabetes, left ventricular developed pressure and rate of rise and rate of decrease of ventricular pressure was also found to be lower with oleuropein treatment than with the control in one study (A.A. Nekooeian, Khalili, Khosravi, ). A daily supplementation of ~30 mg was also found to reduce both systolic and diastolic blood pressure in women (Moreno‐Luna et al, ).…”
Section: Role Of Oleuropein In Treatment Of Metabolic Syndromementioning
confidence: 91%
“…Oleuropein has been shown to reduce malondialdehyde (I. Andreadou et al, ; Khalili et al, ; Z. Janahmadi, Nekooeian, Moaref, & Emamghoreishi, ), play a role in countering the pathogenesis, potentially protect the body against further rises in insulin resistance and, in a best‐case scenario, even have a reversing effect. Oleuropein maintained or increased antioxidant erythrocyte SOD levels (A.A. Nekooeian, Khalili, Khosravi, ; A.A. Nekooeian, Khalili, Khosravi, ; Khalili et al, ; Z. Janahmadi et al, ). Furthermore, multiple studies have demonstrated the beneficial effects on antioxidants on the development of heart disease.…”
Section: Role Of Oleuropein In Treatment Of Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies have identified the cardioprotective effect of oleuropein mediated by its antioxidant property in different kinds of models [812]. Furthermore, Campolo et al have reported that oleuropein could represent a possible treatment against secondary events of intestinal ischemia/reperfusion injury through anti-inflammatory and antiapoptotic pathways [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nekooeian and coworkers found that oleuropein reduced blood glucose, serum malondialdehyde, blood pressure, infaract size, coronary effluent creatine kinase-MB and coronary resistance in type 2 diabetic rats. It also reduced left ventricular developed pressure, erythrocyte superoxide dismutase, rate of rise and rate of decrease of ventricular pressure 34 . Fig.3 …”
Section: Phenylpropanoid: Oleuropeinmentioning
confidence: 91%